Secondary Leukemia After Chemotherapy and/or Radiotherapy for Gynecologic Neoplasia. Issue 2 (1st February 2014) - Shimada, Takako; Saito, Toshiaki; Okadome, Masao; Shimamoto, Kumi; Ariyoshi, Kazuya; Eto, Takako; Tomita, Yui; Kodama, Keisuke
Abstract : Objective: Secondary leukemia is a known complication of chemotherapy and radiotherapy. It was generally recognized that leukemia secondary to chemotherapy was due to the use of alkylating agents in the treatment of ovarian cancer. Recently, many types of chemotherapeutic agents have been used in the treatment of gynecologic malignancies in addition to ovarian cancer. We analyzed the clinical characteristics and outcome of patients with recent onset of secondary leukemia after the treatment of gynecologic cancer to consider the diagnosis and management of secondary leukemia. Materials and Methods: We reviewed the clinical charts and follow-up data of patients with gynecologic malignancies treated in the past 20 years. During this period, 2482 newly diagnosed invasive gynecologic cancers were treated in our institution. All patients with secondary leukemia were analyzed for clinical background, latency period (interval between the diagnosis of primary carcinoma and the development of leukemia), treatment, and outcome. We also reviewed the literature for secondary leukemia under gynecology using the PubMed. Results: Four patients were found to have developed secondary leukemia after the treatment of gynecologic malignancies during this period. The cumulative risk of secondary leukemia was approximately 0.38%. All patients received platinum-based chemotherapy. Two patients received combination chemotherapy and/or bone marrow transplantation, and 1 of these 2 patients lived more than 6 years but died of recurrent ovarian cancer. Conclusions: Long survival time might be expected in patients who show complete response to bone marrow transplantation and/or combination chemotherapy for secondary leukemia. In recent years, we have aggressively used various types of anticancer drugs for the treatment of not only ovarian cancer but also uterine cervical cancer and endometrial cancer. Physicians need to keep in mind the risk of secondary leukemia in the follow-up of long-term survivors after several courses of chemotherapy and radiotherapy.